Transcrição cooperativa de genes ribossomais em Escherichia coli usando um modelo estocástico e dependente de sequência - Nakajima, Rafael Takahiro [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The process that produces messenger RNAs from DNA sequences is called transcription, and these reactions are catalyzed by the RNA polimerase enzyme. Many different experimental techniques have been applied to investigate this process including biochemical techniques, optical and magnetic tweezers, atomic force microscopy and single molecule florescence. These biochemical process studies showed that many RNAP molecules operate simultaneously on a single DNA strand. The number of different molecules depends on cellular demands, concentration of free RNAPs, promoter strength and the presence of transcription factors. Escherichia coli ribosomal genes are a popular experimental model to investigate the transcription process. These genes are essential to cell physiology, and they are strongly expressed. There are evidences that some cellular mechanisms collaborate to accelerate their transcription. In this work we investigate the RNAP collaborative transcription in E. coli ribosomal genes using a stochastic and sequence dependent model proposed by our group. The chemical reactions were simulated using a model based on the Gillespie algorithm. This methodology is a good compromise between computational cost and biological realism and includes some ingredients that were missing in previous theoretical studies. The model considers back and forward tracking elongation and it identifies pauses by determining the dwell time on specific sites. The model also predicts abortive transcription and transcription acceleration due to collaborative RNAP interaction. The E. coli rrnB ribosomal operon sequence was simulated by varying (i) the number of RNAP (R) on the DNA strand, (ii) the interaction force between two colliding RNAPs (F) and (iii) the concentration of nucleoside triphosphate ([NTP]). Our results are promising for F =15 pN, R = 50 and [NTP] ...

Transcrição é o processo catalizado por um complexo enzimático, RNA polimerase (RNAP), responsável pela síntese de RNA mensageiro a partir de uma sequência de DNA. Diferentes estudos experimentais foram realizados para investigar esse processo, como técnicas bioquímicas, de pinça ótica ou magnética, microscopia de força atômica e fluorescência de molécula única. Com os estudos bioquímicos, por exemplo, sabe-se que várias RNAPs podem transcrever uma sequência simultaneamente. O número de diferentes moléculas depende da necessidade da célula, número de RNAP livres, regeneração do promotor e fatores de transcrição. Um dos sistemas mais investigados para o estudo desse processo é a síntese dos genes ribossomais em Escherichia coli. Os genes ribossomais são fundamentais na fisiologia dos organismos, são expressos abundantemente e existem evidências da aceleração da transcrição devido ao comportamento colaborativo entre as RNAPs. Neste trabalho, propomos simular a transcrição múltipla dos genes ribossomais em E. coli com o modelo estocástico e dependente de sequências desenvolvido em nosso laboratório. As reações químicas foram simuladas utilizando o algoritmo de Gillespie. Essa metodologia apresenta uma boa relação entre custo computacional e realismo biológico e inclui alguns parâmetros não utilizados em estudos teóricos prévios. O modelo considera o alongamento em back e forward tracking, identificando os sítios de pausas e colisões entre RNAPs, determinando o tempo de permanência e predizendo a ocorrência de transcrição abortiva ou a aceleração da transcrição devido ao fenômeno colaborativo entre múltiplas RNAPs. A sequência do operon ribossomal rrnB da E. coli foi simulada variando o número de RNAP (R), a força de interação entre RNAPs (F) e a concentração de nucleosídeo trifosfato ([NTP]). Nossos resultados mostraram-se promissores quando utilizamos uma...
Keywords: Escherichia coli; Reação em cadeia da polimerase; Análise estocástica; Seqüenciamento de nucleotídeo; Marcadores genéticos; Genetic markers; Nucleotide sequence